1983
DOI: 10.1002/bbpc.19830870512
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Tritium in Cold‐Worked Palladium

Abstract: The mobility of hydrogen in cold-rolled palladium specimens of different degree of plastic deformation was measured by employing the tritium tracer method. -In one set of experiments the temperature dependence of the diffusivity was determined at very low hydrogen to metal ratios below aboutIn another set of experiments the influence of precharged hydrogen on the tritium mobility was investigated at constant temperature. -The diffusion of tritium as a tracer in presence of hydrogen and within an imperfect latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
7
32
0
Order By: Relevance
“…In the experiment reported by Higelin et al [66], D became larger at temperatures below 75 K when the mass of H isotopes decreased. On the contrary, the quantum-TST-based D values, which were overall in good agreement with experimental values [64][65][66][67], did not clearly follow this trend. It is noted that those obtained from the DFT-based PIMD calculations in the previous study [22] agreed better with experimental values than the present MLP-based results at low temperatures (below 75 K).…”
Section: H-isotope Diffusivities From Quantum Transition-state Theorysupporting
confidence: 49%
“…In the experiment reported by Higelin et al [66], D became larger at temperatures below 75 K when the mass of H isotopes decreased. On the contrary, the quantum-TST-based D values, which were overall in good agreement with experimental values [64][65][66][67], did not clearly follow this trend. It is noted that those obtained from the DFT-based PIMD calculations in the previous study [22] agreed better with experimental values than the present MLP-based results at low temperatures (below 75 K).…”
Section: H-isotope Diffusivities From Quantum Transition-state Theorysupporting
confidence: 49%
“…Krimmel et al [23], for instance, shows that tetrahedral sites have considerably higher energy. Trap sites, on the other hand, were shown to provide spacious, flat potential wells for hydrogen and, therefore, much lower vibrational frequencies [20,40,45]. The flatness of the bottom of the octahedral site is that minima would develop around the edge of the site which add together to give flat bottom of the potential well.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that under the influence of hydrogen, sintering of finely dispersed Pd can occur even at temperatures as low as 330 K [19]. Furthermore, enhanced mechanical stress or cold working [20] applied to the β-phase of palladium hydride may also cause particle growth and can lead to an enhanced defect density such as dislocations in the precious metal [21][22][23][24]. This may result in pronounced hysteresis effects of the hydrogen adsorption/desorption isotherms or the kinetics of hydrogen storage and release [7,8,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SANS measurements presented here are not sensitive to the trapping interaction at very low bulk solubility levels. Trap binding energies have also been inferred from tritium diffusion measurements in 30 and 50 pct cold-worked Pd by Sicking et al [18] A representative binding energy of 0.2 eV was found by these authors.…”
Section: Discussion and Summarymentioning
confidence: 85%